“We called it lockdown school”: a reflexive thematic analysis of the experiences of young people transitioning from primary to secondary school during the COVID-19 pandemic - Watson, Louise (2022)
Transition from primary to secondary school is generally experienced by young people as a significant event (Zeedyk et al., 2003), the success of which is associated with a range of long-term outcomes (e.g. West et al., 2010). Young people transitioning during the coronavirus pandemic have done so at a highly unusual time, which may have made transition more challenging (Bagnall et al., 2022). It is important to understand young people’s perspectives of transition, both as they have the right to be heard and as their perceptions can influence the process and success of transition (Divya Jindal-Snape & Cantali, 2019). This study aimed to understand young people’s experiences and perceptions of transition during the pandemic, as well as what they feel would help to support them in the future.